Cultural responsiveness in applied behavior analysis: Self‐assessment. Issue 2 (10th March 2022) - Beaulieu, Lauren; Jimenez‐Gomez, Corina
Abstract : Culture has a substantial impact on a wide range of behaviors related to behavioral research and services such as rapport building, preferences for specific targets and treatments, communication, and even the quality of health care. The need for professionals in the field of applied behavior analysis (ABA) to incorporate culturally responsive practices is underscored by the current and projected increase in diversity in the United States. Further, the update to the Ethics Code (BACB, 2020) supports addressing diversity in behavior analytic practice. Self‐assessment of one's values, biases, and culture are a critical step in delivering culturally responsive services. The purpose of this paper is three‐fold: a) to introduce a framework for cultural responsiveness in ABA, b) to showcase research and practice recommendations from within and outside the field of ABA in the area of self‐assessment, and c) to inspire research in self‐assessment to support cultural responsiveness in ABA.